Retrospective analysis of the us oil spill struggle experience - V. S. Kharchenko (Путеводитель предпринимателя)
The article is devoted to the retrospective analysis of the largest oil spill consequences. Special attention is drawn to the consequences of the accident in the Gulf of Mexico in 2010 on the oil platform «Deepwater Horizon». The actions of the US government in dealing with the oil spill risks are analyzed.